Determining the effect of restricted feed intake on developing pigs weighing between 150 and 250 lb, fed two or six times daily - J D Schneider; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2006)
Two 42-d studies were conducted to evaluate the effect of restricted feed intake and feeding frequency on the performance of pigs weighing from 150 to 250 lb (initially 148 lb in Exp. 1 and 155 lb in Exp. 2). Our objective was to use the limit-fed finishing pig as a model for gestating sows who are also limit fed. In both experiments, pigs were housed in a 6 ×10 ft pen with half solid cement and half slatted flooring, and with one nipple waterer. The diet consisted of a diet based on cornsoybean meal, formulated to 1.15% TID lysine (1.29% total lysine) and 1,494 kcal of ME/lb. Energy and lysine were supplied to pigs to target an average growth rate of 1.75 lb/d, based on NRC (1998) values. Pigs were fed by dropping similar amounts of feed, either 2 or 6 times per day, by an Accu-Drop Feed Dispenser (AP Systems, Assumption, IL) on the solid cement flooring with ad libitum access to water. In Exp. 1, there was an increase (P<0.01) in ADG and a decrease (P<0.02) in F/G for pigs fed similar amounts of feed 6 times per day, compared with pigs fed 2 times per day. In Exp. 2, increasing the feeding frequency of pigs fed a restricted diet from 2 to 6 times per day improved ADG (P<0.02) and F/G (P<0.03). These studies indicate that increasing the frequency of feeding may improve the metabolic efficiency of the growing pig fed a restricted diet. More research is needed to determine whether the greater gain is due to improved efficiency or whether there is another reason, such as a decrease in feed wastage.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Pigs; Feeding frequency; Restricted intake; Swine